Joitakin osia maailmasta : valokuvataide - arkitaide 2000. - Kaila, Jan; Finnish Museum of Photography, Helsinki; Galerie Anhava, Helsinki; Galleria Artina, Helsinki; Galleria Bakeliittibambi, Helsinki; Galleria Kari Kenetti, Helsinki; Gallery of Academy of Fine Arts, Helsinki; Photographic Gallery Hippolyte, Helsinki (Helsinki : [s.n.], 2000)
Backstrom, Miriam ; Dijkstra, Rineke ; Ekeberg, Jonas ; Fischli & Weiss ; Graham, Paul ; Kearney, Frances ; Männikkö, Esko ; Tillmans, Wolfgang ; Mäkipää, Tea ; Hölttä, Heini ; et al.
some parts of this world, Finnish museum of photography, Helsinki, april - june 2000
kunstcatalogus